Analisis Penggunaan Kapasitor Bank Untuk Meningkatkan Faktor Daya Pada Ruangan MCC di PT. X Purwakarta - Permadi, Yahya; Santoso, Dian Budhi (Jurnal Ilmiah Wahana Pendidikan, 2023)
A factory requires a large amount of electrical power to perform its production process. But with many inductive loads such as Electric motors make the reactive power appear large. Reactive power Large can result in decreased power factors that will be detrimental company. One solution to overcome this problem is with the installation of capacitor banks. This research uses the method simulation on ETAP software to determine the effect of use capacitor banks on the electrical system. The results of this study are: Comparison of conditions when the electrical system uses and does not using capacitor banks. . Power factor value ( changed from 0.8 to 0.9. There was a 4.4 A decrease in grades current (A). In the active power value there is an addition of 1.7 kW. And there is an addition of 1.9 kVA to the apparent power value.